A Case Study On RN Konsult Sdn. Bhd. - Ahmad, Abd Razak (1998)

(untitled)
RN Konsult Sdn Bhd was set up in 1995 by its founders; Abdullah and Dennis from UK. The company was set up to provide engineering consulting services for the construction and other related industries. The company's founders had hoped to establish RNK as a centre of excellence for Bumiputra professionals to service the domestic as well as the regional markets. The SWOT analysis had revealed encouraging opportunities for the company on most of its external environmental factors. And most of the internal factors analysed were also found to have contributed to the strength of the company. The SPACE analysis had positioned the company in a competitive posture where it was operating in an unstable and competitive environmental conditions. It was recommended that the company adopt a pause strategy or proceed with caution in a short term and in a long term adopt a growth strategy through concentration via horizontal integration. It was also recommended for the company to team up with DSP, UK and venture into specialised high-tech projects such as the IT industry and the MSC related sectors.